Development on mathematical model of convective boundary layer flow of viscoelastic fluid with microrotation effect under constant wall temperature thermal condition over a bluff body - Laila Amera, Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (Akademi Sains Malaysia, 2019)
This paper presents the development of mathematical model on the flow of viscoelastic fluid associated with microrotation properties under boundary layer approximation. The respective fluid, also known as viscoelastic micropolar fluid is a member of the non-Newtonian fluid family that contains microstructure while displaying the characteristic of being viscous and elastic. Due to the intricate nature of the fluid and enhanced with the fact that the fluid flows over a bluff body, a complex mathematical model is proposed. The governing equations are derived from the three fundamental physical principals upon which all fluid dynamics are based and later expressed as two-dimensional boundary-layer coordinate. The complexity of the model is reduced after undergoing the boundary layer and Boussinesq approximation. Before it is solved numerically, the mathematical equations of the respective model are subjected to another transformation where the associated equations are changed into dimensionless form and can be written in the simplest form of ordinary or partial differential equations.